Ideological Framings and Linguistic Representations of the Palestinian-Israeli Conflict in UNGA 2025 Speeches - Mahardhika Zifana; Adi Hidayat; Hanifah Oktarina (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2026)
The Palestinian-Israeli conflict remains one of the most contested issues in international diplomacy, with discourse surrounding the conflict functioning as a crucial arena in which geopolitical power relations are constructed, negotiated, and contested. This study investigates how Global North countries, Muslim-majority states, and Global South countries articulate their ideological positions and linguistic representations of the conflict through speeches delivered at the United Nations General Assembly (UNGA) in 2025. Unlike the United Nations Security Council, whose structure privileges major powers through veto authority, the UNGA allows broader participation from both dominant and marginalized states, thereby making it an important arena for examining competing geopolitical narratives. The urgency of this investigation is further intensified by growing international polarization following the escalation of violence in Gaza and the increasing use of genocide accusations within diplomatic discourse. Employing Fairclough's three-dimensional Critical Discourse Analysis (CDA) and Halliday's Systemic Functional Linguistics (SFL), this study aims to reveal the relationship between micro-level grammatical choices and macro-level geopolitical orientations. The findings reveal systematic disparities among the state groups analyzed. The United States tends to background Israeli military actions while foregrounding Hamas, using the events of October 7, 2023, as the principal framework for its security-oriented interpretation. In contrast, Pakistan, South Africa, and Brazil explicitly use the term “genocide,” while Indonesia foregrounds humanitarian suffering without explicitly employing the term. Pakistan's discourse incorporates personalized narratives of victimization, whereas South Africa adopts a predominantly legal-institutional framing grounded in international law. The United Kingdom, meanwhile, manifests hegemonic positioning through a discourse of shared responsibility that enables simultaneous condemnation of humanitarian violations and preservation of strategic alliances. Consequently, this study demonstrates that contestation over the Palestinian-Israeli conflict is not merely a disagreement over political events, but also a broader struggle for dominance over international discourse itself. The relationship between 142 countries supporting genocide-related accusations and a single veto-holding power further illustrates the widening gap between international normative consensus and the realities of geopolitical power during a period of hegemonic crisis. Methodologically, this research demonstrates how systematic linguistic analysis can ground ideological interpretation in observable grammatical patterns, while theoretically positioning Palestinian-Israeli discourse as a metonym for wider contestation over whether international order should be governed by legal universalism, moral-religious principles, or security pragmatism aligned with hegemonic interests.